2020
DOI: 10.3354/dao03477
|View full text |Cite
|
Sign up to set email alerts
|

High occurrence rate of xanthomatosis and nephrocalcinosis in aquarium-housed Atlantic wolffish Anarhichas lupus and spotted wolffish A. minor

Abstract: The Atlantic wolffish (AW) and the spotted wolffish (SW) are long-lived fish found in the North Atlantic and Arctic oceans and are respectively classified as special concern and threatened species, mainly due to fisheries bycatch. To better understand health issues associated with the care of these species in public aquaria, reports from all necropsies performed in 2 zoological institutions between 2009 and 2019 were reviewed (31 AW and 8 SW). These wolffish were fed with a similar fish-based diet and kept in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The calculi analysed by infrared spectroscopy from two adult specimens of southern flounder Paralichthys lethostigma revealed that the stones were 100% calcium phosphate carbonate, in one fish and 100% calcium hydrogen phosphate dehydrate, in other fish (Applegate Jr et al, 2016). In fact, calcium phosphate was reported, by different authors, to be the commonly encountered component of calculi (Bazin et al, 2007; Chandrajith et al, 2006; Scheinman, 2003), including in other species of fish (Béland et al, 2020; Modica et al, 1993; Nowak & Battaglene, 1996). The possibility that the calculi were formed mainly by calcium oxalate (CaC 2 O 4 ) (taking into account the proportion of the elements found in our study) was discarded because calcium oxalate is usually dark brown or black (Scheinman, 2003), whereas calcium phosphate is light in colour, it develops in alkaline urine and it is dissolved in acidic urine.…”
Section: Discussionmentioning
confidence: 99%
“…The calculi analysed by infrared spectroscopy from two adult specimens of southern flounder Paralichthys lethostigma revealed that the stones were 100% calcium phosphate carbonate, in one fish and 100% calcium hydrogen phosphate dehydrate, in other fish (Applegate Jr et al, 2016). In fact, calcium phosphate was reported, by different authors, to be the commonly encountered component of calculi (Bazin et al, 2007; Chandrajith et al, 2006; Scheinman, 2003), including in other species of fish (Béland et al, 2020; Modica et al, 1993; Nowak & Battaglene, 1996). The possibility that the calculi were formed mainly by calcium oxalate (CaC 2 O 4 ) (taking into account the proportion of the elements found in our study) was discarded because calcium oxalate is usually dark brown or black (Scheinman, 2003), whereas calcium phosphate is light in colour, it develops in alkaline urine and it is dissolved in acidic urine.…”
Section: Discussionmentioning
confidence: 99%
“…Nephrocalcinosis, a disease of aquaculture that has been known for almost 50 years ( Landhoilt, 1975 ), is a renal pathology where a mechanistic understanding of the kidney`s function in acid-base regulation will be critical. Nephrocalcinosis is a widespread disorder found in salmonids ( Gillespie and Evans, 1979 ; Harrison and Richards, 1979 ; Smart et al, 1979 ; Fivelstad et al, 1999 ; 2003 ; 2018 ; Klykken et al, 2022a ; Minarova et al, 2023 ), Nile tilapia ( Oreochromis niloticus; Chen et al, 2001 ; 2003 ), sea bass ( Dicentrarchus labrax; Arciuli et al, 2015 ), Atlantic cod ( Gadus morhua ; Damsgard et al, 2011 ), spotted wolffish ( Anarhichas minor ; Foss et al, 2003 ; Béland et al, 2020 ), clownfish ( Amphiprion ocellaris ; Blazer and Wolke, 1983 ), cobia ( Rachycentron canadum ; Klosterhoff et al, 2015 ), southern flounder ( Paralichthys lethostigma; Appelgate et al, 2016 ), Atlantic wolffish ( Anarhichas lupus ; Béland et al, 2020 ), longsnout seahorse ( Hippocampus reidi Ginsburg; Lewisch, et al, 2013 ), lumpfish ( Cyclopterus lumpus ) and ballan wrasse ( Labrus bergylta ) ( Erkinharju et al, 2021 ), and is listed as one of the most prevalent perturbations in Norwegian salmonid culture, particularly with respect to land-based productions of large smolt and post-smolts ( Sommerset et al, 2022 ). The physiological perturbations underlying precipitation of minerals in the kidneys are probably related to elevated concentrations in the diet or in the water of the constituents involved in forming the precipitate, principally calcium, magnesium, and phosphate ( Smart et al, 1979 ), and/or because changes in the water chemistry cause changes in internal physiology which promote the formation of these “kidney stones”.…”
Section: Relevance For Aquaculturementioning
confidence: 99%
“…Additionally, chronic health diseases such as xanthomatosis and nephrocalcinosis have been reported in aquarium populations by Béland et al [63], and nephrocalcinosis (Figure 3 below) is commonly observed in Norwegian broodstock [Beirão J., pers. comm.].…”
Section: Health and Diseasesmentioning
confidence: 99%
“…comm.]. Béland et al [63] attributed these problems to unbalanced diets, especially lipid and mineral content, but recognized that more information is needed to understand the actual causes. Meanwhile Chabot et al [6] reported hepatic lipidosis in on-growing and young adult fish fed a commercial feed with 15-18% lipid content.…”
Section: Health and Diseasesmentioning
confidence: 99%